PSYCHOPHYSIOLOGICAL FOUNDATIONS OF LOVE: HOW NEUROBIOLOGY AFFECTS EMOTIONAL TIES IN THE FAMILY (Psychology Travelogs, 2025)
The article is devoted to an interdisciplinary analysis of love as a complex psychophysiological phenomenon that underlies emotional ties in family relationships. In this paper, love is viewed not only as a cultural, social, or psychological construct, but also as a biologically determined process with clear neurophysiological correlates. This approach allows for a deeper understanding of the mechanisms of forming and maintaining emotional attachment between partners, parents, and children.The article also describes the psychophysiological mechanisms that contribute to the preservation of emotional intimacy in long-term relationships, including joint leisure rituals, bodily contact, verbal affirmations of affection, and shared emotional experiences. The importance of an integrated approach to the study of love, combining the knowledge of neuroscience, psychology and family therapy, is emphasized. The influence of hormonal background on the interaction of family members, especially in critical periods: stressful situations, conflicts, or in conditions of loss of emotional contact, is revealed. It is shown how the activation of certain brain structures - in particular, the hippocampus, the amygdala and the prefrontal cortex - regulates the reactions of attachment, care and emotional regulation.The expediency of using the achievements of neuropsychology in the practice of psychological counseling and psychotherapy of families, in particular when working with couples in crisis situations or building healthy partnership models, is substantiated. The prospects for further research that would allow for more accurate diagnosis of emotional bonding disorders and the development of effective strategies for its restoration are indicated.As a result, love appears as a psychophysiological resource that plays a key role in maintaining the psychological well-being of the individual and the stability of the family system as a whole.
Keywords: psychophysiology of love; neurobiology of emotions; family relationships; psychological health; life satisfaction; family; love